Potassium (de‐)insertion processes in Prussian blue particles: ensemble versus single nanoparticle behaviour - Zampardi, G; Sokolov, S; Batchelor-McAuley, C; Compton, R (Wiley, 2017)
Potassium (de-)insertion from Prussian Blue (PB) is investigated at the single and multi-particle scale. The electrochemical behaviour is found to differ between the two measurement types. At the single particle level oxidation of the PB nanoparticles with concomitant K+ deinsertion occurs more readily than the associated reduction, relating to K+ insertion. In contrast, the cyclic voltammetry of PB in a composite electrode containing conductive additives and polymeric binder suggests the opposite behaviour. Implications for assessing battery materials are discussed.